Pelatihan Pemanfaatan Lahan Pekarangan Rumah dalam Meningkatkan Ketahanan Pangan Daerah Perbatasan Negara Kampung Mosso - Tommi Tommi; Lalu Panji Imam Agamawan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Kampung Mosso is one of the villages located in the Jayapura city government area and is a border area between the Republic of Indonesia and Papua New Guinea. The people in Kampung Mosso work as farmers. The agricultural commodities cultivated in the village are sago, corn, bananas, cassava, etc. However, agriculture in the village is still only to meet the needs of life. Not many people in the village have cultivated agriculture, especially food crops, optimally. Therefore, this community service will try to offer a solution, namely training in the use of home ground land as a strategy to increase food security in border areas. The results of this community service showed that two groups of people in Kampung Mosso were able to cultivate fish and vegetables in buckets, but another group was not able to cultivate fish and vegetables in buckets. The suggestion that needs to be done from this activity is intensive assistance and monitoring to several community groups so that they become more proficient in agricultural and fisheries cultivation.